2007
DOI: 10.1097/01.aog.0000265215.87717.8b
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of and Risk Factors for Recurrence in Women With Ovarian Endometriomas

Abstract: The total rAFS score, but not rAFS stage, is a risk factor for recurrence of both endometrioma and dysmenorrhea, indicating that the rAFS stage has little prognostic value. The existence of a completely random recurrence period may be a universal phenomenon, with its duration and the magnitude of recurrence risk determined by patient characteristics and quality of care. The second phase of much higher recurrence risk may reflect successful reseeding, reimplantation, and regrowth of ectopic endometrium. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
111
4
14

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(144 citation statements)
references
References 32 publications
15
111
4
14
Order By: Relevance
“…It may arguable that incomplete surgery occurs in advanced endometriosis due to access difficulties.In agreement with other authors [5,6], we also identified a younger age at surgery as a risk factor for endometriosis' recurrence. This may be related to an aggressive form of endometriosis present in younger women or to higher estrogen levels.…”
Section: Commentssupporting
confidence: 93%
See 1 more Smart Citation
“…It may arguable that incomplete surgery occurs in advanced endometriosis due to access difficulties.In agreement with other authors [5,6], we also identified a younger age at surgery as a risk factor for endometriosis' recurrence. This may be related to an aggressive form of endometriosis present in younger women or to higher estrogen levels.…”
Section: Commentssupporting
confidence: 93%
“…The inconsistencies found in literature may be due to the complexity of endometriosis itself or to widespread methodological problems in the current studies: (i) limited and/or heterogeneous samples, (ii) few studies conducted with a second-look surgery, (iii) failure to control for endometriosis stage and symptomatology, as well as (iv) use of improper statistical analyses. Although some authors have considered recurrence of pain (dysmenorrhoea, dyspareunia or chronic pelvic pain) [3,5] ultrasound findings [3,[5][6][7] or increased CA125 levels [3,5] to be the definition of endometriosis recurrence, there is still absence of a standardised definition.…”
Section: Introductionmentioning
confidence: 99%
“…''Unfortunately, there is no permanent cure for this condition, so it often requires a life-long management plan with the goal of maximizing the use of medical treatment and avoiding repeated surgical procedures'', reports the American Society of Reproductive Medicine [3]. Lesions and symptoms very frequently return after medication is discontinued or after conservative surgery is performed, a fact which frustrates both patients and clinicians [4] and is estimated to occur in 30-50 % of cases within 2-5 years [2,[5][6][7][8][9][10]. The American College of Obstetricians and Gynecologists Practice Bulletin suggests that the true recurrence rate must be even higher than the rate generally reported in literature, because most publications report symptomatic disease only [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a classification of the stages of endometriosis by the American Fertility Society, this classification is seen as helpful in the area of fertility but of a lesser benefit to pain considerations 39;40 . More recently the disease is classified with respect to four categories: peritoneal in location, nodular and invasive, ovarian endometriomas and uterine adenomyosis [41][42][43][44] . This latter condition represents a developmental abnormality in which the abnormal endometrial location is within the actual wall of the uterus.…”
Section: Laparoscopy For Endometriosismentioning
confidence: 99%